(untitled) (Global Journal of Science Frontier Research, 2021)
Annotation-In the CIS countries, dietary supplements are regularly consumed by less than 2% of the population. While in Europe and the United States this figure exceeds 90%. In India and China, supplements are becoming part of the complex therapy of various pathologies. Currently, various dietary supplements based on honey have been developed using traditional ingredients that go well with honey, such as nuts, fruits, berries, and medicinal plants. However, there is currently little research on the production of honey-based functional foods using non-traditional ingredients of animal origin. One of these ingredients is maral breeding products. In Chinese medicine, dietary supplements based on pant and honey are widely used. However, in Kazakhstan, there are no studies on the development of technologies for creating dietary supplements based on combining honey and domestic maral breeding products.